Generator Step up Transformer Overvoltage Protection in ЕPS Power Plants - Mrvić, Jovan; Vukelja, Petar; Simić, Ninoslav (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
This paper presents the current state of the overvoltage protection of generator transformers in power plants of the Power Company of Serbia (EPS) and gives a critical overview of their overvoltage protection. Recommendations for the purpose of its control are provided. Improved overvoltage protection of power transformers in the EPS is suggested. A critical review of the state of earthing points of the generator transformers is also given.